2013
DOI: 10.1103/physreva.88.022518
|View full text |Cite
|
Sign up to set email alerts
|

Nonperturbative approach for the electronic Casimir-Polder effect in a one-dimensional semiconductor

Abstract: We present the electronic Casimir-Polder effect for a system consisting of two impurities on a one-dimensional\ud semiconductor quantum wire. Due to the charge transfer from the impurity to a one-dimensional conduction band, the impurity states are dressed by a virtual cloud of the electron field. The attractive electronic Casimir\ud force arises due to the overlap of the virtual clouds. The Van Hove singularity causes the persistent bound state (PBS) to appear below the band edge even when the bare impurity s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 37 publications
3
15
0
Order By: Relevance
“…This gives a strong coupling with field modes with frequencies in the proximity of the gap. We will now consider two specific cases: a 1D case where we use relations (23), (24), (25) for a onedimensional crystal (we will discuss later on about validity and limits of the 1D approximation), and an isotropic 3D case where these relations are assumed valid for any direction of the wavevector k.…”
Section: Resonant Interatomic Force In the Photonic Crystalmentioning
confidence: 99%
See 3 more Smart Citations
“…This gives a strong coupling with field modes with frequencies in the proximity of the gap. We will now consider two specific cases: a 1D case where we use relations (23), (24), (25) for a onedimensional crystal (we will discuss later on about validity and limits of the 1D approximation), and an isotropic 3D case where these relations are assumed valid for any direction of the wavevector k.…”
Section: Resonant Interatomic Force In the Photonic Crystalmentioning
confidence: 99%
“…Following the same procedure and approximations used above for the isotropic case, using the 1D dispersion relation (24) in the effective mass approximation, the k integral in (18) after some algebra becomes…”
Section: Resonant Interatomic Force In the Photonic Crystalmentioning
confidence: 99%
See 2 more Smart Citations
“…We have applied this theory to open quantum systems to study dissipation processes of a discrete quantum state interacting with a continuum with a finite bandwidth. We have revealed that the decay is nonanalytically enhanced when the discrete state is located closely to the bandedge of the continuum, and, as a result, it shows a nonanalytic decay process [47][48][49][50]. Therefore, in order to describe the DCE of a hybrid quantum system, it is important to study the competition between the parametric amplification and the resonance instability which will be clarified only when we take into account the effect of the energy-dependent self-energy.…”
Section: Introductionmentioning
confidence: 99%